Four cases of equine bone lesions caused by Pythium insidiosum - MENDOZA, L. (1990)
PYTHIOSIS is usually a granulomatous disease of skin and subcutis in horses (Austwick and Copland 1974; Miller and Campbell 1982; Mendoza and Alfaro 1986), and cattle (Miller, Bruce and Archer 1985), of skin and intestinal tract in dogs (ONeill-Foil, Short, Fadek and Kunkle 1984; Miller 1985), and of skin and blood vessels in man (Sathapatayavongs et a1 1989). The disease is caused by Pythium insidiosum, a microorganism in the class Oomycetes, kingdom Protista (de Cock et al 1987). P. insidiosum was previously known under the names Hyphomyces destruens (Bridges and Emmons 1961). Pythium sp (Austwick and Copland 1974) and P gracile (Ichitani and Amemiya 1980). It is also known as swamp cancer, leeches, bursatte, summer sores, espundia and others (de Cock et a1 1987). Pythiosis in horses is usually associated with the end of the rainy season in tropical and subtropical countries. P. insidiosum develops its life cycle in stagnant water producing biflagellated zoospores that penetrate into the horse through open skin (Miller 1983). After two days, successful zoospora skin penetration, one may observe a swelling area of 5 mm in diameter that increasing rapidly until it reaches 100 to 200 mm in diameter within about two weeks. Lesions two to five months old are commonly reported in Costa Rica (Mendoza and Alfaro 1986), usually due to fruitless treatments. Surgical therapy is used widely to treat this disease (Miller 1981). However, it is not practical on limbs because critical anatomical structures are located in these areas (McMullan et a1 1977). Furthermore, lesions can reappear if the necrotic masses called 'leeches' or 'kunkers' which contain the hyphae of this oomycete microorganism, are not removed completely. Immunotherapy (vaccination with products derived from P. insidiosum) have been successful in Australia and Costa Rica to treat horses in early pythiosis, but not in chronic stages (Miller 1981; Mendoza and Alfaro 1986). In addition, treatment with Amphotericin B and iodine has also been reported (McMullan 1977), but Amphotericin B is expensive and time consuming; iodine treatment requires many hours of attention daily, and both have toxic side effects.